'Interaction structures' between depressed adolescents and their therapists in short-term psychoanalytic psychotherapy and cognitive behavioural therapy. (July 2019) - Calderon, Ana; Schneider, Celeste; Target, Mary; Midgley, Nick
Objective: Identify the core 'interaction structures' between therapists and depressed adolescents within and across two common forms of psychotherapy. Method: A total of 70 audio-recorded psychotherapy sessions representing short-term psychoanalytic psychotherapy (STPP) and cognitive behavioural therapy (CBT) with youth aged 12–18 years old were coded with the Adolescent Psychotherapy Q-set (APQ), a newly developed instrument. Data included different therapist-patient dyads and stages in treatment and were analysed with cluster analysis. Results: Three distinct interaction structures between therapists and depressed adolescents: two influenced by the therapists' techniques and one more influenced by the young people's attitude to therapy. Conclusion: When there is a collaborative working relationship between therapists and depressed young people, the therapy process is influenced by the therapists' techniques; while when there is a poor working relationship, the techniques used by therapists of different theoretical orientation become more similar with the aim of engaging the young person in the process.